Production of artemisinin in shoot cultures of Artemisia cinairradiated callus - Aryanti . (Indonesian Journal of Pharmacy, 2010)
Artemisinin  is  an  antimalaria  agent  that  is  only  found  in Artemisia  sp. medicinal  plant.  This  compound  is  occurred  at  very  low  level  in  that  plant. Irradiated callus of Artemisia cinahave been conducted by the dose of 40 Gy to improve  artemisinin content  in shoot  cultures.  Regeneration  of irradiated  callus to  shoot  cultures  formation  has  been  successful  in  Murashige  &  Skoog  (MS) medium  combined  with  Naphtalene  Acetic  Acid  (NAA)  1  mg/g,  Benzyl  Amino Purin (BAP) 2 mg/L and 15 % coconut water. Ten mutant lines of shoot cultures have  been  analyzed  for  the  artemisinin  content.  The  artemisinin  content  of mutant lines were higher than the original plant. The highest artemisinin content is  5  mg/g  found  in  mutant  line  number  404,  this  line  also  has  wider  leaf  area than original plant.Key word : artemisinin, Artemisia cina, shoot cultures, irradiated callus